ATTITUDE TOWARDS BLOOD DONATION AMONG UNDERGRADUATE ENGINEERING STUDENTS OF SRM UNIVERSITY, KATTANKULATHUR, KANCHEEPURAM DISTRICT - Malini, Hema (Innovare Journal Health Sciences, 2018)
ABSTRACT Introduction: Safe blood is a critical component in improving health care and in preventing the spread of infectious diseases globally. Millions of lives are saved each year through blood transfusions, yet the quality and safety of blood transfusion is still a concern particularly in the developing countries. Objective: To assess the attitude towards blood donation among Engineering students. Methodology: Quantitative research approach and descriptive research design was adopted for the study. The study was conducted among the undergraduate Engineering students of SRM University.Â  A Total 150 Undergraduate Engineering students who fulfilled inclusion criteria. were selected as samples by adopting non probability purposive sampling technique.. Three Â point Likert scale developed by the investigator was used for assessing the attitude of undergraduate students regarding blood donation. Results: Majority of the students (93.35%) had favorable attitude towards blood donation and 6.7% had moderately adequate attitude.. Conclusion: Nurses need to take up the responsibilities to create awareness among the students about blood donation. Key words: Blood donation, attitude, students, health care, blood transfusion.